The Relationship Between Nutritional Statuses and Stress Levels on The Menstrual Cycle in Adolescent Woman at SMAN 3 Sidoarjo - Devy Putri Nursanti; Eri Puji Kumalasari; Asruria Sani Fajriah; Gufron Wahyudi (Journal for Quality in Public Health, 2023)
Psychological factors, hormonal disorders, genetics, organic disorders and nutritional status. Nutritional status is a very influential factor in a woman's menstrual cycle. Inadequate nutritional intake causes menstrual irregularities in most adolescent girls. In addition,  the stress level factor is the cause of menstrual disorders. Excessive secretion of stress hormones can damage cells, tissues, and other organs. One of the most visible effects of stress is menstrual cycle irregularities in adolescent girls. Prove the relationship between nutritional status and stress levels on the menstrual cycle in adolescent girls at SMA Negeri 3 Sidoarjo. Type of survey analytical research  with a cross sectional  approach using Propotional Random Sampling sampling techniques  with inclusion criteria, a total of 88 respondents with a division of 28 respondents from X grade, 29 respondents in class XI and 31 respondents in class XII. The analysis used to assess variables is the chi square and logistic regression statistical test.In this study, an SPSS statistical test using chi square obtained the results of the correlation analysis of the relationship between nutritional status and the menstrual cycle obtained ρ < α results (0.000 < 0.05), while the correlation of the relationship between stress levels and menstrual  cycles obtained ρ < α results (0.002 < 0.05), so it means that H1 accepted means that there is a significant relationship between nutritional status and stress levels with the menstrual cycle of adolescent girls in SMA 3 Sidoarjo.